Wakefulness (Not Sleep) Promotes Generalization of Word Learning in 2.5‐Year‐Old Children. Issue 2 (20th August 2013) - Werchan, Denise M.; Gómez, Rebecca L.
<x xml:space="preserve">Abstract</x> Sleep enhances generalization in adults, but this has not been examined in toddlers. This study examined the impact of napping versus wakefulness on the generalization of word learning in toddlers when the contextual background changes during learning. Thirty 2.5‐year‐old children (M = 32.94, SE = 0.46) learned labels for novel categories of objects, presented on different contextual backgrounds, and were tested on their ability to generalize the labels to new exemplars after a 4‐hr delay with or without a nap. The results demonstrated that only children who did not nap were able to generalize learning. These findings have critical implications for the functions of sleep versus wakefulness in generalization, implicating a role for forgetting during wakefulness in generalization.